The Effect of Work Environment and Transformational Leadership on Teacher Performance at Public Elementary Schools - Hartanto, Kurniawan Widhi; Ginting, Rosalina Br.; Ariyanto, Lilik (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to examine the partial and simultaneous effects of work environment and transformational leadership on teacher performance in public elementary schools in Limbangan District, Kendal Regency, Central Java, Indonesia. This research employed a quantitative approach with a correlational design. The population consisted of 221 teachers from 30 public elementary schools, from which 142 respondents were selected using proportional random sampling. Data were collected through structured questionnaires measuring teacher performance, work environment, and transformational leadership. The collected data were analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis to examine both partial and simultaneous effects of the independent variables on teacher performance. The findings revealed that the work environment has a significant positive effect on teacher performance (r=0.733; R²=53.7%; p<0.001), indicating that a supportive work environment contributes substantially to improving teacher performance. Transformational leadership also demonstrated a significant positive effect (r=0.824; R²=68.0%; p<0.001), showing a stronger contribution than the work environment. Furthermore, work environment and transformational leadership simultaneously exert a significant influence on teacher performance and explain a substantial proportion of its variance. The results indicate that transformational leadership is the dominant predictor of teacher performance, highlighting the strategic role of school principals in enhancing teacher effectiveness. Therefore, efforts to improve educational quality should prioritize strengthening transformational leadership while fostering a supportive work environment to achieve sustainable improvements in teacher performance.